Identification of the Target for a Transition Metal-α-Amino Acid Complex Antibiotic Against Mycobacterium smegmatis - Karpin, George W.; Merola, Joseph S.; Falkinham, Joseph O. (Frontiers in Pharmacology, 2021)
Spontaneous mutants of Mycobacterium smegmatis strain mc2155 resistant to 1-PG (iridium-L-phenylglycine complex), an antimycobacterial antibiotic, were isolated. Based on the discovery that some 1-PG-resistant mutants (1-PGR) were also resistant to high concentrations of clarithromycin (≥ 250 µg/mL), but no other anti-mycobacterial antibiotics, the 23S rRNA region spanning the peptidyl transferase domain was sequenced and mutations shown to be localized in the peptidyl transferase domain of the 23S rRNA gene. Measurements showed that 1-PG bound to ribosomes isolated from the 1-PG-sensitive parental strain, but the ribosome binding values for the 1-PGR mutant were significantly (P = 0.0474) reduced.